BAMBU CENDANI SEBAGAI IDE PENCIPTAAN KURSI TERAS - Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
Designers are required to be able to develop themselves in making a product that can attract public interest. People need a place to rest and relax, one of the facilities is to relax using a patio chair. Terrace chairs as a relaxing facility need a comfortable and functional design, as well as aesthetic value.The purpose of making this design is to create creative and innovative patio chairs. Patio chairs are sitting facilities for a means of relaxing or relaxing on the terrace.The porch chair that the penulus makes takes the bamboo stick as its shape structure with marble finish so that it is able to display a dynamic impression, the dowel construction is used for easy assembly. so that creative and innovative patio chair designs are created. The main function of the patio chairs is to provide comfort when relaxing The porch chair that the penulus makes takes the bamboo stick as its shape structure with marble finish so that it is able to display a dynamic impression, the dowel construction is used for easy assembly. so that creative and innovative patio chair designs are created. The main function of the patio chairs is to provide comfort when relaxing